Metabolites from the mangrove-derived fungi : Acremonium sp. PSU-MA70 and Pestalotiopsis sp. PSU-MA92 and PSU-MA119 - Aekkachai Rodglin (Prince of Songkla University, 2013)
Thesis (M.Sc., Organic Chemistry)--Prince of Songkla University, 2010